Makna dan Peran Konsep Halal dalam Membangun Kepercayaan dan Loyalitas Konsumen serta Pedagang - Samsudin (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
Halal retail is not only determined by certification, but also by the process of negotiating the meaning of halal at the point of sale through labels, claims, seller narratives, and shopping experiences. This research aims to explain how the process shapes consumer trust and loyalty and how traders manage halal credibility. The methods used were qualitative case studies with purposive-snowball sampling, data collection through semi-structured interviews, observation, and document review, and thematic analysis with triangulation and member checking. The results showed that consumers verified halal claims using a combination of formal evidence and social evidence, then adjusted the intensity of verification based on perceived risks and situational context. Merchants build trust through information disclosure, coherent explanations, consistency of service, product curation, and complaint recovery. Stable halal negotiations lower uncertainty, strengthen religious security, and encourage buybacks and recommendations, so loyalty emerges as an accumulation of doubt settlement. These findings underscore the importance of a relational approach in local halal retail governance and loyalty enhancement strategies.